Effects Of Terrorism On The Turnover Intentions And In-Role Job Performance Of Government Primary School Teachers In Pakistan - Memon, Ubedullah (2022)
Since the last decade, terrorist attacks on the government primary schools of Pakistan surged rage and fear among the teaching fraternity. Terrorists’ barefaced daylight attacks on schools infiltrated teaching fraternity to continue their jobs and efficiently perform job-related tasks. The classroom walls riddled with bullet holes constantly reminded teachers about the impending potential danger. The present study exposed teachers’ fragile state in Pakistan’s terrorism-affected government primary schools through multisource time-lagged data. The present study’s findings confirmed the detrimental role of teachers’ perceived threats of terrorism and job dangerousness in escalating their job stress. Furthermore, the present study intercepted the negative effect of teachers’ job stress on their turnover intentions and in-role job performance through the moderating effect of perceived resilience. The results confirmed the significant and positive association of teachers’ perceived threats of terrorism and job dangerousness with their job stress. Further, teachers’ job stress significantly performed multiple mediations in the research model of the present study. First, the mediating role of teachers’ job stress between perceived threats of terrorism and their turnover intentions was found significant. Second, the mediating role of teachers’ job stress between perceived threats of terrorism and their in-role job performance was also found significant. Third, the mediation function of teachers’ job stress between job dangerousness and their turnover intentions was found significant.